2007
DOI: 10.1002/col.20294
|View full text |Cite
|
Sign up to set email alerts
|

Color‐emotion associations and color preferences: A case study for residences

Abstract: This study examines existing beliefs about ''color'' focusing on color-emotion associations by discussing how color can be used as a way of communicator to fulfill human needs in residences. Fifty people from various age groups participated in the study. They were asked to match a list of adjectives with the proper color samples from the catalogue of a quite popular color producer firm in Turkey. Results indicate that there is a strong dependency between the choice and use of green at residences. Emotional res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
152
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 13 publications
21
152
1
8
Order By: Relevance
“…This may contradict Manav (2006) and Kaya -Crosby (2006) whose findings show that differences in color connotations are associated with the individuals' knowledge and experience.…”
Section: Colour Connotationsmentioning
confidence: 74%
“…This may contradict Manav (2006) and Kaya -Crosby (2006) whose findings show that differences in color connotations are associated with the individuals' knowledge and experience.…”
Section: Colour Connotationsmentioning
confidence: 74%
“…A variety of studies have been conducted for the color's impact on the users' immersion level and psychology when the users experience the content. For example, Banu [32] showed that the bright colors such as green mitigate the negative factors such as eye-fatigue and motion sickness. Moreover, color plays the role of expressing favor and repulsion from people, and it helps people to be aware of their various emotions (e.g., bright colors help to lift the user's emotion) [33].…”
Section: Background Colormentioning
confidence: 99%
“…Renk seçimi konusunda cinsiyet, yaş, kültür, içinde bulunulan bölgenin tarihi ve coğrafi özellikleri önem kazanmaktadır. Kadın ve erkeklerin renk izlenimi ve renk kullanımı konusundaki tercihlerinde fark gözlenmektedir (Frieling 1979;Holzschlag 2000;Manav 2007;Saito 1996;Manav 2010). Bu sonuçlar, kızların odalarının duvarlarında pembenin, erkeklerde ise mavinin kullanılabileceğini göstermektedir.…”
Section: Sonuç Ve öNerilerunclassified